Determination of optimum management strategy for Küre Mountains national park in Turkey - Daşdemır, İsmet; Güngör, Ersin; Daşdemir, İsmet; Güngör, Ersin (Nova Science Publishers, Inc., 2011)
There are 39 national parks in Turkey and totally 877.771 hectares area is used for this aim. One of them is Küre Mountains National Park (KMNP), which has 37.000 hectares area and was decelerated in the year 2000. It is the first national park which its boundaries determined by contribution and participation of different society groups in Turkey. In this study, it is aimed to determine optimum management strategy for KMNP by turning out preferences of different society groups (local villagers, public institution and nongovernmental organization representatives, potential tourists) and providing their participation to the management process effectively. To realize this aim, it has been studied to develop a management model taking into consideration social and economic values as well as ecological values. It is also investigated a management model such as to manage conservation areas by participation principle and to use income from conservation areas for developing local villagers. In the study, the present situation of the national park is turned out by SWOT analysis, and some alternative management strategies (scenarios) for the national park are developed based on the findings in this stage. The four attributes such as managing type, entrance fee, sharing income and administrative structure which each one has three sub-levels are taken into consideration while developing alternative management scenarios. The nine orthogonal alternative management strategies based on these attributes and their sub-levels are submitted to 462 interviewees selected by layer-random sampling method. The interviewees arranged these strategies according to their preferences. The preference results are evaluated by conjoint analysis, and thus the optimum management strategy is determined for the national park as a managing system with the balance conservation use, taking US$ 10 entrance fee from visitors, sharing the 70% of income to the national park management and its 30% to local villagers, and administrating with the cooperation of state, nongovernmental organizations and local villagers. Taking into consideration the optimum management strategy in the management plan of KMNP, which is though preparation, will help the plan to be applicable and dynamic structure, prevent conflicts among local villagers and the national park management, and thus, to contribute to sustainable management of the national park. © 2010 by Nova Science Publishers, Inc. All rights reserved. © 2014 Elsevier B.V., All rights reserved.
Keywords: Conjoint Analysis; Küre Mountains National Park; National Park Management Strategy; Participation; Swot Analysis; Turkey.